Morphology and Anatomy of the Inflorescence Axis and Flowers in Arenga Porphyrocarpa (Palmae) - E.B. Hidajat (Journal of Mathematical and Fundamental Sciences, 1976)
Abstract. In Arenga Porphyrocarpa the vegetative axis is terminalised by the onset of the hapaxanthic flowering axis. This is accompanied by a reduction of leaf size. The part of the axis beyond the last node transforms into a female inflorescence which consists of a system of rachillae on which the individual flowers are attached. Male inflorescences develop afterwards on the remaining nodes but may also develop from the most distal node later on. Additional female inflorescence may develop at lower nodes. Monopodial branching is not confined to  the reproductive axis only but occurs also in the branching system of  the inflorescence. Although flowers occur solitary at the female rachilla or in pairs generally at the male rachilla, ontogenetic examination shows that the basic pattern is a flower cluster of three. At the female rachilla only the central latest developing flower matures while at the male rachilla only the two marginal flowers develop. Presumably the type of branching in a flower cluster follows a sympodial pattern. In the female flower, the stipitate gynoecium contains two ovules which not may be of the same size. The stigmatic region leads to a cleft like stylar canal. Three staminodia occur at the female flower. The male flower carries 19-20 stamens each one consisting of a short filament and a long latrorse anther. Ringkasan. Pada Arenga porphyrocarpa, sumbu vegetative berakhir dengan perkembangan sumbu reproduktif yang mengikuti cara berbunga hapaxanthic. Hal tersebut diiringi oleh reduksi gradual ukuran daun. Bagian sumbu di atas buku terakhir berkembang menjadi perbungaan betina yang terdiri atas sistim rachilla dengan kuntum-kuntum bunga. Perbungaan jantan berkembang sesudah itu pada buku-buku lain tetapi dapat pula berkembang pada buku paling distal. Demikian pula perbungaan betina lain kemudian dapat berkembang pada buku lebih rendah. Percabangan monopodial tidak hanya terdapat pada sumbu reproduktif melainkan juga pada sistim percabangan dalam perbungaan. Meskipun kuntum bunga terdapat sendiri-sendiri pada rachilla betina atau umumnya berpasangan pada rachilla jantan, namun pengamatan ontogeny menunjukkan bahwa pola dasar bagi pertumbuhan adalah kelompok yang terdiri atas tiga kuntum bunga. Pada rachilla betina hanyalah bunga tengah, yang berkembang paling akhir, tumbuh jadi dewasa. Pada rachilla jantan hanya kedua bunga tepi tumbuh sampai dewasa. Diduga bahwa percabangan dalam kelompok bunga mengikuti pola sympodial. Pada bunga betina gynoecium stipitate beris dua buah bakal biji yang tidak sama besar. Daerah stigma bersambung dengan saluran stylus berbentuk celah. Tiga helai staminodia berbentuk filament terdapat pada bunga betina. Bunga jantan memiliki 19-20 stamen yang masing-masing terdiri atas filamen pendek dan anther panjang dan latrors.